Infrastructure development, inequality, and employment in Sub-Saharan Africa from the professional perspectives of Kenya, Ghana, and Tanzania - Mohamad Zreik; Badar Alam Iqbal; Munir Hassan; Sharifah Zannierah Syed Marzuki (Discover Global Society)
Abstract This study investigates the challenges and opportunities in infrastructure development, inequality, and employment in Sub-Saharan Africa. There is a critical gap between infrastructure planning and execution, exacerbated by inadequate funding, bureaucratic hurdles, and a lack of technical expertise, leading to profound inequality in infrastructure and employment opportunities, particularly affecting rural and marginalized communities. The study aims to identify the mismatch between current job market needs and the workforce's skills, analyse the impact of rapid population growth and insufficient educational initiatives, and propose solutions for integrated infrastructure planning and equitable policy development. This research employs qualitative semi-structured interviews and thematic analysis using NVivo to gain in-depth insights into the institutional characteristics influencing infrastructure development, inequality, and employment. Findings reveal significant disparities in infrastructure and employment opportunities, with rural and marginalized communities being disproportionately affected. There is a notable mismatch between job market needs and the available workforce skills, further complicated by rapid population growth and inadequate educational initiatives. The study recommends an integrated approach to infrastructure planning that encompasses sustainability, accessibility, and equitable distribution. Policies should address inequality, ensure equitable access to infrastructure benefits, and align education and skill development with the evolving job market. Leveraging public–private partnerships is also suggested to accelerate infrastructure development efficiently. This paper contributes to the discourse on infrastructure, inequality, and employment in Sub-Saharan Africa, providing a roadmap for addressing these intertwined challenges through integrated policy initiatives.